Digital provenance and material metadata: Attribution and co-authorship in the age of artificial intelligence. (December 2018) - Doyle, Shelby; Senske, Nick
This speculative essay examines a single drawing, produced in a collaboration between the authors and a Turtle robot, in a search for methods to evaluate and document provenance in artificial intelligence and robotic design. Reflecting upon the layers of authorship in our case study reveals the complex relationship that already exists between human and machine collaborators. In response to this unseen provenance, we propose new modes to document the full range of creative contribution to the design and production of artifacts from intellectual inputs to digital representations to physical labor. A more comprehensive system for artificial intelligence/robotic attribution could produce counter-narratives to technological development which more fully acknowledge the contributions of both humans and machines. As artificially intelligent design technologies distinguish themselves with distinct capabilities and eventual autonomy, a system of embedded attribution becomes the basis for human–machine collaboration, indeterminacy, and unexpected new applications for existing tools and methods.